The Influence of Internal and External Human Resources and Motivation on Training Productivity - Cendani Alfanizha Hidma; Mesiono Mesiono; Toni Nasution (Goodwood Publishing, 2026)
Purpose: This study aims to analyze the influence of internal human resources, external human resources, and motivation on the productivity of education and training (diklat) activities at the Religious Education and Training Center in Medan. Research Methodology: This research was conducted at the Religious Education and Training Center in Medan using a quantitative approach with a survey method. Data were collected from 45 respondents through questionnaires. The analysis techniques included classical assumption tests, simple and multiple linear regression, as well as partial and simultaneous hypothesis testing using statistical software. Results: The findings show that partially, internal human resources and motivation do not have a significant effect on productivity, while external human resources have a significant effect. Simultaneously, all variables significantly influence productivity with a significance value of 0.023 (< 0.05). However, the contribution of these variables is relatively low, with a coefficient of determination of 20.6%. Conclusions: The study concludes that the productivity of training activities is influenced by multiple factors, where external human resources play a more dominant role compared to internal factors and motivation. Limitations: This study is limited by the small sample size and the focus on a single institution, which may affect the generalizability of the results. Contributions: This research contributes to the field of human resource management and training productivity by providing empirical evidence for policymakers and institutional managers, particularly in improving the effectiveness of training programs in religious education institutions.